ANALISIS RASIO UNTUK MENGUKUR KINERJA PENGELOLAAN KEUANGAN DAERAH DI KABUPATEN SAROLANGUN TAHUN 2011-2013 - Coriyati Coriyati (Jurnal Dinamika Manajemen, 2016)
The purpose of this study was to determine the performance of local government financial management based on financial ratio analysis in the Sarolangun Regency APBD and to determine the development of Sarolangun Regency APBD revenues. The type of research used is descriptive research using ratio analysis method. The results showed that the independence ratio during the three fiscal years was very low with an average of 4.26 percent, the effectiveness ratio during the three fiscal years was very effective with an average of 102.2 percent, the average activity ratio during the three fiscal years in operational expenditure of 66.77 percent and capital expenditure of 27.12 percent, the ratio of expenditure management has a budget surplus every year and has an average of 104.85 percent, and the PAD growth ratio has an average growth of 0.13 percent and Revenue has an average growth of 7.45 percent, while the operating expenditure ratio has an average growth of 6.46 percent and the capital expenditure ratio has an average growth of 2.99 percent. The development of the revenue of the Sarolangun Regency APBD has increased every year.